The Effectiveness of Virgin Coconut Oil on the Decrease of Blood Glucose Levels on Gestational Diabetes Mellitus - Noer Saudah; Indah Lestari; Catur Prasastia Dewi Lukita; Sahrir Sillehu; Joel Rey U. Acob (Journal of Ners and Midwifery, 2021)
Gestational Diabetes Mellitus (GDM) was medical complication that occurs during pregnancy and caused preterm labor.Â  Efforts reduce blood glucose levels and improve pancreatic performance must be safe both for mother and fetus. The research aimed to prove VCO can reduce blood glucose levels in GDM. The research design was quasi-experimental with one group pre-test and post-test. The research started on March to September 2020. The population was pregnant mother with GDM from two hospitals in Mojokerto East Java. The sample was 46 respondents with purposive sampling. The treatment given was VCO at a dose of 5 ml, 6 times a day and lowcarb diet. The instrument used to measure the fasting blood glucose was glucose stick.Â  The data was analyzed with paired t-test. The result showed blood glucose levels before intervention average of 155.19 mg/dL and after 153.50 mg/dL. The t-test value 14.442 and p value 0.000 which meant that VCO and low carb diet was more effective in reducing blood glucose levels on GDM. The administration of VCO with a low carb diet is an effort to restrict glucose intake in the body without hypoglycemia. It is safe to use for both mother and fetus as an alternative non-pharmacological therapy on GDM and prevent preterm labor